Pengaruh Cekaman Kekeringan dan Umur Panen Terhadap Pertumbuhan dan Kandungan Xanthorrhizol Temulawak (Curcuma xanthorrhiza roxb.) - Khaerana; Ghulamahdi, Munif; Purwakusumah, Edi Djauhari (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
The research was conducted from November 2005 until May 2006 to determine growth and production of the Curcuma xanthorrhiza based on agronomical, physiological variables, and bioactive (xanthorrhizol) content.  The experiment was arranged in a completely randomized design with two factors and three replications.  The first factor consisted of 4 level of drought stress i.e: 100% field capacity (FC) (as control), 50% FC started at 2 weeks before harvesting (wbh),  50% FC started at 4 wbh,  and 50% FC started at 6 wbh.  The second factor comprised of 2 harvest times i.e. 5 months and 7 months.  The result showed that drought stress decreased plant growth and productivity, but increased accumulation of proline.  The harvesting time significantly increased the agronomic character, but did not significantly increase proline content.  The older samples contained more xanthorrhizol than the younger samples.   Key words: Curcuma xanthorrhiza, drought stress, harvesting time, plant growth,  xanthorrhizol.